Plan comercial para una tienda e-commerce caso Tcuido.pe - Traverzo Vila, Miguel Angel (2023)
The Tcuido Brand began its operations in July 2020 due to the situation, which the country was going through the pandemic. Tcuido is a brand of the company Igoolt S.A.C. whose main business units are the electronics, telecommunications and software industries in which they have been operating since 2008. The board of directors decided to enter the retail industry through a virtual store with the Tcuido brand, which allowed a nationwide delivery of products related to the disinfection of environments, food, and objects, in order to have a better biosafety protocol for Peruvian families and companies. Between July and December 2020, they met the sales quotas projected by the board of directors when starting operations; however, at the beginning of 2021 sales began to fall; because this category was related to cases of contagion of the coronavirus; Therefore, a project to import a new category of products was proposed, which was related to the care and well-being of people. Therefore, the initiative was given to import oral care category products, as a proposal, to improve the company's profitability and to allow the brand to continue expanding nationally and in the future at a multinational level. The proposed proposal for this project is reflected in a new business plan in order to generate a mínimum profit of 20%; in addition to increasing the quality of life of customers; Therefore, it is desired to increase awareness of health care through social networks; Therefore, the objective is to increase the followers of social networks by 50%, for the next fiscal year of 2024 and the first quarter of 2025.